2021
DOI: 10.1016/j.heliyon.2021.e07190
|View full text |Cite
|
Sign up to set email alerts
|

Study of UV-C treatments on postharvest life of blueberries ‘O'Neal’ and correlation between structure and quality parameters

Abstract: The effect of different doses of 8.3 and 11.4 kJ/m 2 ) on native mycobiota and Botrytis cinerea incidence, micro and ultrastructure, biomechanical properties and weight loss of blueberry fruit cv. O'Neal during 20 days of storage at 8 AE 1 C was evaluated. Decay incidence was significantly reduced by all UV-C light doses for both, native mycobiota and inoculated B. cinerea. The highest UV-C dose studied (11.4 kJ/m 2 ) was the most effective indelaying the onset of fungal and B. cinerea infection (6 and 4 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Various combinations of processes and agents have been explored to enhance the efficiency of antagonistic yeasts. UV-C irradiation, for instance, has been tested as a method to prevent fungal diseases in fruits [187]. A study by Sun et al [188] has shown that UV-C irradiation improves the quality of fruits by increasing the activity of antioxidant enzymes and reducing mycotoxins.…”
Section: Advanced Approaches To Mitigating Post-harvest Diseases and ...mentioning
confidence: 99%
“…Various combinations of processes and agents have been explored to enhance the efficiency of antagonistic yeasts. UV-C irradiation, for instance, has been tested as a method to prevent fungal diseases in fruits [187]. A study by Sun et al [188] has shown that UV-C irradiation improves the quality of fruits by increasing the activity of antioxidant enzymes and reducing mycotoxins.…”
Section: Advanced Approaches To Mitigating Post-harvest Diseases and ...mentioning
confidence: 99%
“…228 UV-C irradiation is one of the methods applied to fruit and has also been tested for preventing postharvest fungal diseases. 229 According to a recent study, it helps to improve the postharvest quality of fruit by boosting the activity of antioxidant enzymes and reducing mycotoxins. 230 Additionally, combination studies with yeasts were also available to demonstrate the method's efficacy when applied alone.…”
Section: Combination With An Agentmentioning
confidence: 99%
“…Apart from agents, different physical methods may be applied with antagonistic yeasts to extend the shelf life of fruits and vegetables and reduce losses due to postharvest mold-related diseases . UV-C irradiation is one of the methods applied to fruit and has also been tested for preventing postharvest fungal diseases . According to a recent study, it helps to improve the postharvest quality of fruit by boosting the activity of antioxidant enzymes and reducing mycotoxins .…”
Section: Combined Application Of Antagonistic Yeasts For Enhanced Bio...mentioning
confidence: 99%
“…Probes previously used to collect penetration parameters of blueberries include needle probes such as the P/2 N (Stable Micros Systems, UK) of 2 mm maximum diameter and 0.39 mm tip diameter (Rivera et al, 2021a;; or the 1.8 mm maximum diameter (item 320398, ZwickRoell, Italy) reported by Giongo et al (2022). Other probes for penetration test include cylindrical flat end probes of 2 mm (Silva et al, 2005;Concha-Meyer et al, 2015;Giongo et al, 2022), 3 mm (Jaramillo-Sánchez et al, 2019Jaramillo-Sánchez et al, 2021), or 4 mm diameter (Giongo et al, 2013(Giongo et al, , 2022.…”
Section: Probes Used On Penetration Testmentioning
confidence: 99%
“…Blueberry rots are one of the most critical threats to blueberry quality as they can greatly impact the market life of fresh blueberries (Forney, 2009). Reductions in rot prevalence have been described when using postharvest technologies, including controlled atmosphere (CA) storage (Forney et al, 2003;Harb and Streif, 2004;Alsmairat et al, 2011;Cantin et al, 2012;Rodriguez and Zoffoli, 2016;Falagan et al, 2020), sulfur dioxide (SO 2 ) (Cantin et al, 2012;Rivera et al, 2013;Saito et al, 2020), ozone (Jaramillo-Sánchez et al, 2019), atmospheric cold plasma (ACP) treatment (Hu et al, 2021), and UV-C light irradiation (Jaramillo-Sánchez et al, 2021).…”
Section: Postharvest Technologies Used To Control Rotmentioning
confidence: 99%